A hybrid intelligent control based cyber-physical system for thermal comfort in smart homes. (31st March 2019) - Zhu, Jiawei; Lauri, Fabrice; Koukam, Abderrafiaa; Hilaire, Vincent; Lin, Yishuai; Liu, Youquan
With the fast development of human society, as environmental issues have drawn incomparable attention, energy efficiency is playing a significant role in residential buildings. Meanwhile, spending more time in homes leads people to constantly improve comfort there. Considering the fact that space heating makes a great contribution to residential energy consumption and thermal comfort, this paper presents a novel hybrid intelligent control (HIC) system to manage space heating devices in a smart home with advanced technologies to save energy while to increase thermal comfort level. The approach combines a meta-heuristic algorithm used to compute a setpoint from the Predicted Mean Vote model with a Proportional-Integral-Derivative controller for indoor temperature regulation. In order to validate the system, computer simulations are conducted and analysed. The results indicate the proposed control system can provide better thermal comfort comparing with other conventional and intelligent control methods, and consume less energy when demand response is considered.